Social Participation of Students with Special Educational Needs in Mainstream Education - Schwab, Susanne; Nel, Mirna; Hellmich, Frank (Taylor & Francis, 2019)
This book provides deep insight into the social situation of students with different kinds of special needs in various European countries. Research findings concerning students' attitudes towards peers with disabilities, and teachers' feedback on students' social behaviour, are also presented. Full inclusion of students with special educational needs in mainstream education requires equity in each student's chances for academic and social-emotional development, and their participation in society. In the context of inclusive education, it is important to take students' social participation into consideration. Are students with special educational needs (SEN) accepted by their peers? Do they interact with their peers during breaks and classes? Do they have friends, or do they feel lonely in their class? This book seeks to answer such questions, seeing social participation as a crucial ingredient, as well as an outcome, of inclusive education. This topic is critical because many previous studies show students with SEN having a high risk of social exclusion. This volume will be of interest to everyone studying special needs education, especially those concerned with future improvement of social participation for all students. This book was originally published as a special issue of the European Journal of Special Needs Education. Chapter 1 is available Open Access at https://www.routledge.com/products/9780367209186.